STUDI OPTIMASI PENENTUAN UNSUR HARA BESI DALAM CAMPURAN TANAH DAN KOMPOS MENGGUNAKAN METODE SPEKTROFOTOMETRI - -, Refilda; -, Suhartini; -, Indrawati (Jurnal Riset Kimia, 2015)
Determination of iron nutrient content in a mixture of soil and compost with spectrophotometric method has been carried out. Metal ions Fe(II) complexed with 0.1% ortho-fenantrolin 2 mL, 0.01 M citric acid as reducing agent using acetat buffer at pH 4.5 and its complex was measured by using spectrophotometer UV/Vis at wavelength 515 nm, the complex stability for was 60 minutes . The highest nutrient of iron with content in soil:compost with ratio of 0.8:0.2 was 0.92% at incubation time 30 days. The lowest iron content in the mixture of soil:compost (1:0) at incubation time for 15 days was 0.58% that obtained by the regression equation y = 95.85x + 0.025 with R2=0.992. The level of nutrient iron in compost obtained lower than the maximum regulated by SNI 2.00%.